2021
DOI: 10.15252/embj.2019104296
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional repression of NFKBIA triggers constitutive IKK‐ and proteasome‐independent p65/RelA activation in senescence

Abstract: The IjB kinase (IKK)-NF-jB pathway is activated as part of the DNA damage response and controls both inflammation and resistance to apoptosis. How these distinct functions are achieved remained unknown. We demonstrate here that DNA double-strand breaks elicit two subsequent phases of NF-jB activation in vivo and in vitro, which are mechanistically and functionally distinct. RNA-sequencing reveals that the first-phase controls anti-apoptotic gene expression, while the second drives expression of senescence-asso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 50 publications
0
41
0
Order By: Relevance
“…n =3 per group, n ≥20 crypts per mouse. (E) Representative IHC images of anti-cleaved caspase 3 and Alcian Blue staining on PSI sections of Δ N and control ( n =3 per group) mice, and of a tissue sample of γ-irradiated control mice (see Kolesnichenko et al, 2021 ). Black arrows point to caspase 3-positive (apoptotic) cells in villi of irradiated controls.…”
Section: Resultsmentioning
confidence: 99%
“…n =3 per group, n ≥20 crypts per mouse. (E) Representative IHC images of anti-cleaved caspase 3 and Alcian Blue staining on PSI sections of Δ N and control ( n =3 per group) mice, and of a tissue sample of γ-irradiated control mice (see Kolesnichenko et al, 2021 ). Black arrows point to caspase 3-positive (apoptotic) cells in villi of irradiated controls.…”
Section: Resultsmentioning
confidence: 99%
“…However, our results show an increase in IKK mRNA using different housekeeping genes with no significant differences between their expressions in the various experimental conditions, suggesting a transcriptional regulation upon treatment with the evSASP. Interestingly, a recent study has shown that during the initial activation of senescence, IKKβ is activated by ATM while in the later stages the sSASP is expressed independently of IKKα/β and proteasome degradation of IκB in spite of depending on the NF‐κB protein p65 (Kolesnichenko et al, 2021). Altogether, this suggests that the activation of NF‐κB is far more complicated than initially thought in the context of senescence and both the sSASP and evSASP.…”
Section: Discussionmentioning
confidence: 99%
“…[56][57][58][59][60][61][62][63] Interestingly, the control of the SASP itself by RELA/p65, which we detected in two sequencing datasets of aging women, has recently been experimentally verified in U2OS osteosarcoma cells. 64 Transcriptome-wide state-of-the-art technologies such as scRNA-seq will help shape our understanding of not just aging, but also therapeutics that potentially target fundamental mechanisms of aging, such as senolytics. As noted earlier, a confounder in these analyses is the generally low expression of the canonical marker of senescence, Cdkn2a/p16 Ink4a , which is clearly detectable by RT-qPCR in the setting of aging, but poses challenges when using transcriptomewide approaches.…”
Section: Discussionmentioning
confidence: 99%